Business students' perceptions of women in management - Frank, Ellen J (Sex Roles, 1988)
This study surveyed 202 undergraduate business majors regarding their perceptions of women in management. Research focused on male and female students' acceptance of women managers, the extent students perceived women managers as being accepted by others, and a comparison of descriptions of the typical male and female manager. Male students were found to be less accepting of women's dual role. Men perceived women managers as being less knowledgeable and possessing poorer managerial skills than male managers. Women managers were perceived as having greater interpersonal skills. Female students showed a greater preference for a male boss. Their descriptions of women managers were more positive regarding competency, but emphasized an interpersonal rather than a task orientation. The conclusion is made that perceptual stereotypes have not radically changed when compared to research reported in the 1970s. © 1988 Plenum Publishing Corporation.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-483-800-573-559 tex.type: [object Object]
Keywords: dept.mgt

Designing and implementing a personnel mis - Frank, EJ (Personnel, 1987)
tex.unique-id: ISI:A1987K654900011
Keywords: dept.mgt; ⛔ No DOI found